Density and function of actin-microdomains in healthy and NF1 deficient osteoclasts revealed by the combined use of atomic force and stimulated emission depletion microscopy - Takahiro Deguchi; Elnaz Fazeli; Sami Koho; Paula Pennanen; Maria Alanne; Mayank Modi; John E Eriksson; Kari V Vienola; Pekka E Hänninen; Juha Peltonen; Tuomas Näreoja (My University, 2022)
Actin and myosins (IIA, IIB, and X) generate mechanical forces in osteoclasts that drive functions such as migration and membrane trafficking. In neurofibromatosis, these processes are perturbed due to a mutation in neurofibromatosis type 1 (NF1) gene. This mutation leads to generation of hyperactive bone-resorbing osteoclasts that increases incidence of skeletal dysplasia e.g. early-onset osteoporosis in patients suffering from neurofibromatosis. To study the density and function of actin clusters in mutated cells we introduce a new approach for combined use of a stimulated emission depletion (STED) microscope with an atomic force microscope (AFM). We resolved actin-cores within actin-microdomains at four typical structures (podosome-belt, podosome raft, actin patches, and sealing zone) for osteoclasts cultured on bone as well as on glass. Densities of actin-cores in these structures were higher on bone than on glass, and the nearest neighbor distances were shortest in sealing zones, where also an accumulation of vesicular material was observed at their center. In NF1 deficient osteoclasts, the clustering was tighter and there was also more vesicular material accumulated inside the sealing zone. Using the STED-AFM system, we measured the condensation of the actin structures in real-time after a bone-coated cantilever was placed in contact with a differentiated osteoclast and found that the condensation of actin was initiated at 40 min, after sufficient local actin concentration was reached. A functional implication of the less dense clustering in NF1 deficient cells was that the adhesion of these cells was less specific for bone. The data and new methodologies presented here build a foundation for establishing novel actomyosin dependent mechanisms during osteoclast migration and resorption.